The concept of complete equality in mufawadah partnership: its recognition and rationale in islamic law - Sadique, Muhammad Abdurrahman (2016)
The emphasis in mufawadah partnership is on realising complete equality in all relevant aspects of the venture where sharing is possible. This has theoretically necessitated, among other things, total equality of capital possessed and invested by each partner in the venture, equality in transactional powers, and each partner being a guarantor for the liabilities of the other, in addition to bearing mutual agency. With the extraordinary nature of this contract, it is exceedingly questionable that such a partnership is feasible, if not at its inception, at least in continuation. Thus, the purpose in the detailed analysis of mufawadah in works of Islamic law appears to be highlighting the differences between mufawadah and ‘ inan, complementing the study of the latter, which is the most common form of contractual partnership.